Back to Osborne. Sequential Protein Extraction and LC-MS Analysis for the Characterization of the Holm Oak Seed Proteome - Romero-Rodríguez, M.Cristina; Maldonado-Alconada, AnaM.; Valledor, Luis; Jorrin-Novo, JesusV. (Plant Proteomics SE - 27, 2014)
It is impossible to capture in just one experiment all or most of the total set of protein species that constitute the cell’s proteome. Thus, according to our results, and even considering that they depend on the experimental system carried out (plant, yeast, fungi, or bacteria), the best protein extraction protocol yielded less than 20 % of the total amount of proteins, as determined by the Kjeldahl method. For this reason, protein cataloguing and the whole proteome characterization require the use of firstly, fractionation techniques at the cellular, subcellular, protein, or peptide level, and secondly, the use of complementary approaches. Within our current research on Holm oak (Quercus ilex subsp. ballota), we aim to characterize its seed proteome. For that we have optimized an experimental workflow in which the Osborne sequential protein extraction (Osborne, Science 28:417–427, 1908) is combined with downstream electrophoretic protein separation or shotgun MS analysis. In general, it can be used to study any plant seed, as well as to investigate on seed maturation and germination, genotype characterization, allergens identification, food traceability, and substantial equivalence, among others.
Keywords: Holm oak proteomics; Osborne; Seed proteomics

Proteotyping of Holm Oak (Quercus ilex subsp. ballota) Provenances Through Proteomic Analysis of Acorn Flour - Valero Galván, José; González Fernandez, Raquel; Valledor, Luis; Rafael Cerrillo, Ma.Navarro; Jorrín-Novo, Jesús V (Methods in Molecular Biology Plant Proteomics SE - 49, 2014)
Proteomics has become a powerful tool to characterize biodiversity and natural variability in plant species, as well as to catalogue and establish phylogenetic relationships and distances among populations, provenances or ecotypes. In this chapter, we describe the standard proteomics workflow that we currently use in cataloguing Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) populations. Proteins are extracted from acorn flour or pollen by TCA/acetone or TCA/acetone-phenol methods, resolved by one- or two-dimensional gel electrophoresis, and gel images are captured and analyzed by appropriate software and statistical packages. Quantitative or qualitative variable bands or spots are subjected to MS analysis in order to identify them and correlate differences in the protein profile with the phenotypes or environmental conditions.
Keywords: Holm oak proteomics; Plant biodiversity; Plant proteotyping

Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 23962806
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology

Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª Ma; Abdelly, Chedly; Jorrín-novo, Jesús (Plant Physiology and Biochemistry, 2013)
Phytophthora cinnamomi is one of the agents that trigger the decline syndrome in Quercus spp., this being a serious threat to Mediterranean Holm oak forest sustainability and reforestation programs. Quercus ilex responses to Phytophthora cinnamomi have been studied in one-year olds seedlings from two Andalucía provenances, assessing the physiological water status and photosynthesis-related parameters. Upon inoculation with mycelium a reduction in water content, chlorophyll fluorescence, stomatal conductance and gas exchange was observed along a 90 days post inoculation period in both provenances. The reduction was higher in the most susceptible (SSA) provenance, than in the most tolerant (PCO), being these typical plant responses to drought stress. Leaf protein profiles were analyzed in non-inoculated and inoculated seedlings from the two provenances by using a 2-DE coupled to MS proteomics strategy. Ninety seven proteins changing in abundance in response to the inoculation were successfully identified after MALDI–TOF–TOF analyses. The largest group of variable identified proteins were chloroplasts ones, and they were involved in the photosynthesis, Calvin cycle and carbohydrate metabolism. It was noted that a general tendency was a decrease in the protein abundance as a consequence of the inoculation, being it less accused in the least susceptible, the Northern provenance (PCO), than in the most susceptible, the Southern provenance (SSA). This trend is clearly manifested in photosynthesis, amino acid metabolism and stress/defence proteins. On the contrary, some proteins related to starch biosynthesis, glycolysis and stress related peroxiredoxin showed an increase upon inoculation. These changes in protein abundance were correlated to the estimated physiological parameters and have been frequently observed in plants subjected to drought stress.
From Duplicate 1 (Physiological and proteomics analyses of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) responses to Phytophthora cinnamomi - Sghaier-Hammami, Besma; Valero-Galvàn, José; Romero-rodríguez, Mª Cristina; Navarro-Cerrillo, Rafael Mª; Abdelly, Chedly; Jorrín-novo, Jesús)
Keywords: Gene Expression Regulation; Holm oak decline; Holm oak proteomics; Phytophthora; phytophthora cinnamomi; Phytophthora: physiology; Plant; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: microbiology